Complete genome sequence of a novel gammapartitivirus from Penicillium oxalicum RCEF7482 - Sun, Jing; Wang, Ping; Lu, Hanwen; Yang, Guogen; Huang, Bo (Archives of virology, 2024)
Penicillium oxalicum , an important biocontrol fungus in China, has been a subject of extensive study due to its role in combating various pathogenic fungi. Despite the prevalence of mycoviruses with double-stranded (ds) RNA genomes in filamentous fungi, there has been no screening of mycoviruses in P. oxalicum . In this report, we describe the identification and characterization of a novel dsRNA virus isolated from P. oxalicum , designated as "Penicillium oxalicum partitivirus 1" (PoPV1). The genome of PoPV1 consists of two dsRNA segments, dsRNA1 (1,770 bp) and dsRNA2 (1,584 bp), each containing a single open reading frame (ORF): ORF1 and ORF2. Comparative analysis revealed that the RdRp and CP amino acid sequences of PoPV1 share the highest identity (89.18% and 73.97%, respectively) with those of Penicillium aurantiogriseum partitivirus 1 (PaPV1). Motif analysis based on RdRp amino acid sequences places PoPV1 in the genus Gammapartitivirus within the family Partitiviridae , with a distinctive motif VI (R/KV/ILGDD). Phylogenetic analysis further established a close relationship of PoPV1 to PaPV1, forming a unique clade among the gammapartitiviruses. Consequently, we propose that Penicillium oxalicum partitivirus 1 represents a new species in the genus Gammapartitivirus . This is the first report of a dsRNA virus in P. oxalicum .